Aktivitas Antioksidan Dan Total Fenol Teh Herbal Daun Pacar Air (Impatiens balsamina) Dengan Variasi Lama Fermentasi Dan Metode Pengeringan - Rahmawati, Nur Dyah; , Dr. Nanik Suhartatik, S.TP. M.P (2015)
Tea is a popular drink in the world, usually made from young shoots of tea plant (Camellia sinensis L. Kuntze). Tea products can be produced from the leaves of the Pacar Air, Pacar air leaves containing coumarin compounds, flavonoids, quinones, saponins and steroids. The purpose of this study to know antioxidant activity and total phenolic herbal tea pacar air leaf with variations fermentation and drying methods. This research method with a completely randomized design with two factors: factor 1: fermentation 60 minutes (A1), fermentation 90 minutes (A2), Ferementasi 120 minutes (A3) and factor 2: Methods of drying dried under the sun (B1 ) oven (B2, and roasted (B3). Results showed the highest antioxidant activity in the fermentation 60 minutes with roasted drying method that is 62.436% and the lowest antioxidant activity in the fermentation of 120 minutes with the oven drying method is 45.407%. Total phenol highest in the fermentation 120 minutes with roasted method is 17.479 mg galat/ 100cc, while the lowest total in the fermentation phenol 60 minutes with the oven drying method is 5.723 mg galat/ 100 cc. The antioxidant activity of tea is not linear with total phenol as a result of the combination of the interaction of various compounds antioxidants in the product.